Integrative Holistic Education in Early Childhood at Yaa Bunayya Kindergarten, Bima City - Arinah, Arinah; Yusuf, Abdurrahman; Sadat, Anwar (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
This study aims to determine how the application of integrative holistic education goals in early childhood at Yaa Bunayya Kindergarten, Bima City. The research method used in this research is descriptive qualitative. The data sources used in this study are primary data sources and secondary data sources. The primary data source is the Principal and PIAUD Teacher Yaa Bunayya Bima City. The secondary data sources are data obtained from graphic documents, photographs, films, video recordings, objects and others that can enrich primary data for research collected according to the author's needs. The results of this study indicate that the implementation of integrative holistic education at Yaa Bunayya Kindergarten in Bima City has successfully achieved the expected goals. Children experience significant development in various aspects, including physical, cognitive, social-emotional, language, moral, independence and responsibility. A comprehensive and contextualized approach that considers local culture has a positive impact on children's development. A supportive, safe and loving learning environment is a key cornerstone in achieving these outcomes. The research also shows the importance of collaboration between schools, teachers, parents and communities in supporting integrative holistic education and the need for continuous evaluation to ensure sustainability and improvement of education quality.